The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s004240100565
|View full text |Cite
|
Sign up to set email alerts
|

The coronary endothelium-derived hyperpolarizing factor (EDHF) stimulates multiple signalling pathways and proliferation in vascular cells

Abstract: In the present study we determined whether the endothelium-derived hyperpolarizing factor (EDHF), in addition to its acute effects on vascular tone, activates intracellular signalling pathways other than those associated with Ca2+-dependent K+ channels. EDHF was generated by rhythmic distension of porcine coronary arteries under conditions of combined nitric oxide (NO) synthase/cyclo-oxygenase blockade, and the EDHF-containing luminal incubate was applied to cultured human coronary endothelial or smooth muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 28 publications
(49 reference statements)
2
65
0
Order By: Relevance
“…5 In the present study, we observed that the endothelial cell uncoupling observed 5 to 10 minutes after cell stimulation with either bradykinin or 11,12-EET was not detectable in cells pretreated with inhibitors of MEK, which prevent the activation of ERK1/2. Both bradykinin and 11,12-EET activated ERK1/2 in endothelial cells 30,31 and induced a MEK inhibitor-sensitive shift in the mobility of Cx43 in SDS-PAGE, changes that are indicative of Cx43 phosphorylation. Such observations suggest that the activation of ERK1/2 leads to the phosphorylation of endothelial connexins and promotes cellular uncoupling.…”
Section: Discussionmentioning
confidence: 98%
“…5 In the present study, we observed that the endothelial cell uncoupling observed 5 to 10 minutes after cell stimulation with either bradykinin or 11,12-EET was not detectable in cells pretreated with inhibitors of MEK, which prevent the activation of ERK1/2. Both bradykinin and 11,12-EET activated ERK1/2 in endothelial cells 30,31 and induced a MEK inhibitor-sensitive shift in the mobility of Cx43 in SDS-PAGE, changes that are indicative of Cx43 phosphorylation. Such observations suggest that the activation of ERK1/2 leads to the phosphorylation of endothelial connexins and promotes cellular uncoupling.…”
Section: Discussionmentioning
confidence: 98%
“…CYP 2C9-derived EETs rather than ROS are therefore the most likely mediators of the enhanced cyclin D1 expression and endothelial cell proliferation. DISCUSSION We have demonstrated previously that the CYP 2C9 product, 11,12-EET, activates multiple signal transduction pathways in native and cultured endothelial cells and that overexpression of a CYP 2C epoxygenase enhances endothelial cell numbers (7). Therefore, we set out to elucidate the intracellular signal transduction cascade linking enhanced CYP expression and EET production with proliferation.…”
Section: Role Of the P38 Map Kinase And Jnk In The Cyp 2c9-induced Upmentioning
confidence: 98%
“…Effects of 11,12-EET and H 2 O 2 on Basal JNK Activity and MKP-1 Expression-Since CYP 2C9 generates EETs as well as ROS, both of which can affect the activation of MAP kinases as well as cell proliferation (7,19,20), we compared the effects of 11,12-EET and H 2 O 2 on JNK activity and MKP-1 expression. Stimulation of endothelial cells with 11,12-EET (1 M) elicited a marked and time-dependent decrease in basal JNK activity, which was pronounced 1 h after stimulation (Fig.…”
Section: Role Of the P38 Map Kinase And Jnk In The Cyp 2c9-induced Upmentioning
confidence: 99%
See 1 more Smart Citation
“…well as its metabolites 12(S)-HETE and 11,12-epoxyeicosatrienoic acid activate p38 MAPK in some cell types (Paine et al, 2000;Alexander et al, 2001;Fleming et al, 2001;Reddy et al, 2002). Whether AA and its metabolites mediate the activation of p38 MAPK by a physiological agonist has not been investigated.…”
mentioning
confidence: 99%